The effect of red dragon fruit (hylocereus polyrhizus) juice on leptin levels in overweight model of Sprague Dawley rats - Novia Zuriatun Solehah; Herviana Herviana; Nissa Anggriany; Karina Anindita (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2026)
ABSTRACTBackground: Obesity is strongly linked to elevate leptin levels and oxidative stress, both of which contribute to the development of various metabolic disorders. Leptin, a hormone that regulates metabolism and appetite, becomes less effective in obese individuals due to leptin resistance, thereby exacerbating metabolic dysfunction.Objective: This study aims to evaluate the effect of red dragon fruit (Hylocereus polyrhizus) juice on leptin levels in Sparague Dawley rats using an overweight model.Method: This experimental study used a pre and post-test control group design and involved six treatment groups, including a normal group, a negative control group, a positive control group (orlistat), and three treatment groups receiving different doses of red dragon fruit juice (3.5 g, 7 g, and 10.5 g per 200 g body weight). The intervention was carried out for 14 days following a 14- day induction of obesity using a high-fat and high-carbohydrate diet. Leptin levels were measured before and after the intervention. Leptin examination was performed using the Enzyme-Linked Immunosorbent Assay (ELISA) method, and all data were analyzed using paired t-test, one-way ANOVA, and post hoc tests with a significance level of p < 0.05.Results: The results showed that administration of red dragon fruit juice significantly reduced leptin levels (p<0.001) in all treatment groups. The greatest reduction was observed in the group receiving the 10.5 g dose, with an average decrease of 75.03%, which was nearly equivalent to the orlistat group that reduced leptin levels by 79.93%.Conclusion: Red dragon fruit juice has the potential to serve as a non-pharmacological agent in reducing leptin levels and oxidative stress under obesity conditions, with an effectiveness approaching that of orlistat.Keywords: Red dragon fruit juice; leptin; obesity; sprague dawley rats